High-purity syngas production by cascaded catalytic reforming of biomass pyrolysis vapors. (15th September 2022) - Yang, Hanmin; Cui, Yuxiao; Han, Tong; Sandström, Linda; Jönsson, Pär; Yang, Weihong
Graphical abstract: Highlights: Biomass pyrolysis and in-line cascaded catalytic reforming for syngas production. Applying Pre-reforming (biochar) + Primary reforming (Ni-based) catalysts. 71.28 wt% syngas is obtained, with 89.47 vol% of (H2  + CO) Gas Energy Conversion Efficiency (GECE) of the optimal process was 75.65% Low carbon-footprint hydrogen production: 3 kg-CO2 /kg-H2 produced. Abstract: A novel pyrolysis followed by in-line cascaded catalytic reforming process without additional steam was developed to produce high-purity syngas from woody biomass. The key to the proposed process is the construction of a cascaded biochar + NiAl2 O4 catalytic reforming process in which biochar acts as a pre-reforming catalyst, and NiAl2 O4 acts as a primary reforming catalyst. The large oxygenates in the pyro-vapors are deeply cracked in the biochar layer due to the increased residence time in the hot-biochar bed. The remaining small molecules are then reformed with the autogenerated steam from pyrolysis catalyzed by the reduced Ni 0 species in the NiAl2 O4 catalyst (NiAlO). The results showed that the yield of syngas for the optimized process was 71.28 wt% (including 44.44 mg-H2 /g-biomass and 536.48 mg-CO/g-biomass), and the CO2 yield of the process was only 3 kg-CO2 /kg-hydrogen. High-purity syngas with 89.47 vol% of (H2  + CO) was obtained, and the gas energy conversion efficiency (GECE) of the process reached 75.65%. The study shows that in the cascaded catalytic reforming process, cracking of the large oxygenates and reforming of the small molecules are promoted sequentially in separated biochar + NiAlO catalyst layers, which maximizes the syngas production and improves the activity and stability of the Ni-based catalyst.